2020
DOI: 10.3390/su12166527
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Behavior in Selective Waste Collection: A Case Study Regarding the Determinants from Romania

Abstract: The increase in consumerism due to population growth, excessive advertising and the constant encouragement of buying behavior by advertising media and opinion formers comes with side effects for the environment and public health if it is not properly supported by a sustainable selective waste collection process. In this context, the paper aims at determining the impact of different elements on people’s intention to participate in selective waste collection and on their behavior related to the collection proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Noticeable the average indicator of 0.60 kg / capita / day of household waste generation in Bacau County was higher than in Nowy Sacz County. Jigani et al [32] showed the higher indicator of waste accumulation in Romania. Overall, this ratio has increased, as has the total amount of waste in spite of decrease of amount inhabitants in first mentioned county.…”
Section: Discussionmentioning
confidence: 97%
“…Noticeable the average indicator of 0.60 kg / capita / day of household waste generation in Bacau County was higher than in Nowy Sacz County. Jigani et al [32] showed the higher indicator of waste accumulation in Romania. Overall, this ratio has increased, as has the total amount of waste in spite of decrease of amount inhabitants in first mentioned county.…”
Section: Discussionmentioning
confidence: 97%
“…Although it is difficult to establish the best system, State members should work together towards the identification of common quality management systems. Further, it has been estimated that door-to-door collection schemes deliver better results and are more likely to involve consumers in the sustainable process [90], making them more aware of the waste they produce [91]. Further, door-to-door collection could be easily monitored, and unsustainable consumers are more likely to be subject to fines [92].…”
Section: Separate Collection Techniques and Rates Across Europementioning
confidence: 99%
“…Marketing/sale addition relates to marketing and sales strategies (such as the layout of goods and special offers in supermarkets) that can further affect consumers' behavior (Mondéjar-Jiménez et al 2016). The perceived behavioral control represents the beliefs of individuals regarding the difficulty of reducing their food waste behavior (Ammann et al 2021;Jigani et al 2020).…”
Section: Shopping Control (Food)mentioning
confidence: 99%